Management of Strengthening Student Independence Through Craft Learning by Making Tempe (Qualitative Descriptive Study at SMK Al Ahmad, Warungkondang District) - Amalia, Nelly; Diana, Nenden; Tanti, Tanti; Risgianti, Ricky (Global Education Journal, 2025)
Local values play a strategic role in shaping the character and identity of students, especially in the context of Vocational High Schools (SMK) which prepare students to enter the workforce while maintaining local cultural roots. In Warungkondang District, Cianjur Regency, the tradition of making tempeh has become part of the community's life which is rich in cultural values such as mutual cooperation, hard work, responsibility, and independence. However, in learning practices at SMK Al Ahmad, this local potential has not been fully integrated into the curriculum, especially in the Arts and Crafts (SBDP) subject. In fact, learning based on local wisdom can strengthen the relevance and meaningfulness of the education process. This study aims to analyze how craft learning by making tempeh can strengthen local values and foster student independence. The study used a qualitative approach with a case study method. The subjects of the study included SBDP teachers and grade X students at SMK Al Ahmad. Data collection techniques were carried out through observation, in-depth interviews, and documentation. Data analysis used the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results of the study showed that project-based craft learning of making tempeh carried out in a participatory and contextual manner had a positive impact on strengthening students' independent character. Students showed increased ability in planning, making decisions, solving problems, and increasing self-confidence and responsibility. Strengthening local values through the learning process also fosters appreciation for regional culture and strengthens the relationship between schools and communities. Thus, the integration of local wisdom in craft learning is proven to not only enrich students' learning experiences, but also be an effective strategy in character building. This model can be replicated and developed in other contexts as a contribution to contextual, transformative, and sustainable education.